‘A Prophetic Approach to Bullying Prevention: The Role of ‘Aisyiyah in Central Java - Nuria Siswi Enggarani; Achmad Miftah Farid; Arief Budiono (Greenation Research & Yayasan Global Resarch National, 2026)
Title: Prophetic Approach to Bullying Prevention: The Role of Aisiyah Central Java. Object: 'Aisyiyah as a Muhammadiyah women's organization in Central Java that implements prophetic values.' Aisyiyah is a community organization that also supervises educational institutions, especially in handling bullying issues in Central Java. The handling of complex bullying cases encourages Aisyiyah institutions to address them as autonomous Muhammadiyah organizations. Method: This study uses a non-doctrinal method with a sociological approach. Data from interviews with reliable sources are analyzed using qualitative methods to obtain objective research results. Results: Aisiyah's actions in handling bullying cases in elementary and secondary schools are a form of implementing Islamic values to protect the rights of women and children in educational institutions. The prophetic approach is carried out by accompanying victims of abuse spiritually by religious leaders. Conclusion: The role of 'Aisyiyah in the act of pseudo-autonomy does not contradict the policy of the Regional Government.